2021
DOI: 10.3390/ijms22031219
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals in Gynecological Cancer Prevention

Abstract: Gynecological cancer confers an enormous burden among women worldwide. Accumulating evidence points to the role of phytochemicals in preventing cervical, endometrial, and ovarian cancer. Experimental studies emphasize the chemopreventive and therapeutic potential of plant-derived substances by inhibiting the early stages of carcinogenesis or improving the efficacy of traditional chemotherapeutic agents. Moreover, a number of epidemiological studies have investigated associations between a plant-based diet and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 192 publications
(153 reference statements)
0
17
0
Order By: Relevance
“…Some are polyphenols, terpenoids, and thiols; their effects have been studied in various diseases such as EC. A group of polyphenols found in soybeans and legumes includes flavonoids and isoflavones, such as genistein, daidzein, and glycitein, which have an antiestrogenic effect in the prevention of EC [ 84 ]. A meta-analysis that included epidemiological studies compared a higher intake of isoflavones against a lower intake and found a reduction in the risk of EC [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some are polyphenols, terpenoids, and thiols; their effects have been studied in various diseases such as EC. A group of polyphenols found in soybeans and legumes includes flavonoids and isoflavones, such as genistein, daidzein, and glycitein, which have an antiestrogenic effect in the prevention of EC [ 84 ]. A meta-analysis that included epidemiological studies compared a higher intake of isoflavones against a lower intake and found a reduction in the risk of EC [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis that included epidemiological studies compared a higher intake of isoflavones against a lower intake and found a reduction in the risk of EC [ 85 ]. Another polyphenol compound, epigallocatechin gallate, found in green tea, has been associated with prevention of angiogenesis [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, doxorubicin, loaded in these nanogels, had prolonged circulation time and greater tumor uptake. Epidemiological studies revealed that some of these tumors might be affected by phytochemicals, capable of preventing their development and spread [59]. Human cervical adenocarcinoma (HeLa) cells exposed to piperine displayed growth inhibition either due to a tendency of the cells to be arrested at the G2/M phase or due to increased apoptosis, DNA fragmentation, and cell death, linked with caspase-3 activation and the generation of reactive oxygen species [25].…”
Section: Piperine and Gynecological Cancersmentioning
confidence: 99%
“…During pregnancy, the chances of miscarriage in women with PCOS are more than three times that of women without PCOS. Women with PCOS undergo infertility, resulting in gynaecological cancer [5]. Early detection of PCOS results in saving miscarriage.…”
Section: Introductionmentioning
confidence: 99%